Optimalisasi Teknologi AI untuk Visualisasi Desain Kawasan Pesisir dalam upaya Pengabdian masyarakat pada Permukiman Bajo di Soropia - Ahsan Hidayat; Andi Al Mustagfir; Nahdatunnisa; Tahir, M Arzal; Reksa (FAKULTAS TEKNIK UMKENDARI, 2024)
The traditional Bajo settlement in Soropia, Southeast Sulawesi, represents a cultural heritage that reflects the harmonious relationship between humans and the coastal environment. However, rapid modernization and urbanization have caused morphological transformations in the settlement, risking the loss of local cultural elements. This study aims to develop a settlement design that integrates traditional elements with modern design through Artificial Intelligence (AI). The urgency of this research arises from the pressing need to preserve the Bajo cultural identity, which is threatened by changes in settlement structures, and the lack of visual references that combine cultural elements with innovative design. The main issue faced is the development of settlements that often do not consider the sustainability of local culture. The methodology includes field observations, interviews with the community, literature review, and data visualization using AI technologies such as ChatGPT and Visual Dreaminal. The expected outcome is an AI-based visual guide that can be used for the revitalization of the Bajo settlement, preserving the local cultural identity while meeting the functional needs of the community. This research is expected to contribute to the development of sustainable, culture-based settlement. Keywords: Bajo Settlement, Artificial Intelligence (AI), Cultural Preservation, Sustainable Design, Cultural Identity, Revitalization.